Student teachers’ experience of participating in a research and development project in Norway - Blomsø, Sindre Øyan; Jakhelln, Rachel Elise; Postholm, May Britt (Frontiers in Education, 2023)
This study investigates student teachers’ experience of participating in a research and development project named Learning, Assessment and Boundary-crossing in Teacher Education (LAB-TEd). LAB-TEd is a tripartite collaboration project between student teachers, practice teachers and university teachers from two universities in Norway. Framed by Cultural-Historical Activity Theory, participatory data analysis workshops, known as Change Laboratories, have been used to ensure the relevance of the student teachers’ thesis work for professional development, and to uncover obstacles and barriers to change. Recent research highlights that teachers are typical participants in Change Laboratories implemented in teacher education and schools. There are few studies that highlight student teachers as participants in such interventions, and this may indicate that this is a field of research that is important to investigate. The purpose of the article is to provide insight about how student teachers’ experience participating in a research and development project grounded in CHAT. The data material consists of qualitative interviews with thirty-four student teachers. Findings from this study indicate that student teachers experienced a development journey by participating in the project. The following are the main findings from the study: The student teachers experienced that their own drive and motivation went from self-interest as the driving force for participation, to a more collective understanding. The student teachers first experienced tripartite collaboration as non-existent, later to become tripartite collaboration. The student teachers experienced how their role in the project’s tripartite collaboration developed from serving as a communication link between university and school, to becoming an actual participant. The student teachers also experienced how their role in Change Laboratories changed from being voiceless participants to becoming more equal partners in the project.